Hardware metering - Koushanfar, Farinaz; Qu, Gang (Design Automation, 2001 Proceedings, 2001)
We introduce the first hardware metering scheme that enables reli-able low overhead proofs for the number of manufactured parts. The key idea is to make each design slightly different. Therefore, if two identical hardware designs or a design that is not reported by the foundry are detected, the design house has proof of miscon-duct. We start by establishing the connection between the require-ments for hardware and synthesis process. Furthermore, we present mathematical analysis of statistical accuracy of the pro-posed hardware metering scheme. The effectiveness of the meter-ing scheme is demonstrated on a number of designs.